A model for beam–column corner joints of existing RC frame subjected to cyclic loading. (15th April 2015) - Metelli, G.; Messali, F.; Beschi, C.; Riva, P.
Highlights: A component-based model for external beam–column joints with hooked-end plain bars is presented. We model both the panel shear deformation and the member rotation due to bar slip within the joint. The model leads to a rational definition of the joint shear distortion for limit states of increasing damage. We validated the model by means of test results of full-scale exterior beam–column sub-assemblies. The model allows the drift at incipient collapse of the sub-assemblies to be easily estimated. Abstract: Beam-to-column joints are commonly considered critic regions for RC frames subjected to earthquake actions. When designed for gravity loads only, beam-to-column corner joints strongly affect the global structural behaviour of a frame, and they can be cause of its collapse, as shown by recent earthquakes in Europe. In the paper, a component-based f.e. model for external beam-to-column joints is presented to simulate the seismic behaviour of r.c. existing structures designed without any capacity design criteria (smooth bars with hooked-end anchorages and with no transverse reinforcements in the joint). The joint deformation is modelled by means of two separate contributions, the shear deformation of the panel zone, and the rotation at the interface sections between the joint and the structural members, due to the reinforcing bars' slip within the joint core. The work focuses on the evaluation of the joint strength and stiffness, and it points out the importance of modelling the bar bond slip within the panel zone to describe the actual frame response. The component-based f.e. model is validated by experimental results of tests on beam-to-column corner joints realized according to the construction practice of the 1960s–1970s in Italy, thus confirming the effectiveness of the presented model for the assessment of existing structures.